2014
DOI: 10.1017/s1366728914000698
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and cognition: A focus on mechanisms

Abstract: The goal of my keynote article, “Bilingualism and Cognition” (Valian, 2014), was to resolve the inconsistencies in effects of bilingualism on executive functions, whether the individuals were children, young adults, or old people. To summarize (and sharpen) my argument: 1.Especially in children and young adults, benefits of bilingualism for executive functions are not reliable. In old people, there are benefits for executive functions but contradictory results on delay of cognitive impairment, depending on whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Details of their background information were presented in the first half of Table 2 “background characteristics,” including L2-related factors (tested L2 proficiency, self-rated L2 proficiency, self-rated L2 use, AoA) and more biological and social factors (age, IQ, parents’ education). Such information was collected to ensure that confounding factors (e.g., Dong and Li, 2015; Valian, 2015) would be controlled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of their background information were presented in the first half of Table 2 “background characteristics,” including L2-related factors (tested L2 proficiency, self-rated L2 proficiency, self-rated L2 use, AoA) and more biological and social factors (age, IQ, parents’ education). Such information was collected to ensure that confounding factors (e.g., Dong and Li, 2015; Valian, 2015) would be controlled.…”
Section: Methodsmentioning
confidence: 99%
“…But there have been dissenting voices (e.g., Paap and Greenberg, 2013) or cautious voices (e.g., Hilchey and Klein, 2011) in recent years. This controversy has turned into a hot debate, especially after a recent issue of Bilingualism: Language and Cognition (a series of commentaries on the key article by Valian, 2015) and a recent issue of Cortex (a series of commentaries on the key article by Paap et al, 2015). Experts on the topic have expressed their warnings against methodological flaws (see Paap, 2014, for example), theoretical weaknesses (see Jared, 2015, for example), and interpretation biases (see Morton, 2015, for example).…”
Section: Introductionmentioning
confidence: 99%
“…However, other models assume that some control processes occur outside language processing (e.g., ICM and BIA+). This typically means that language control is part of general cognitive control (for a recent review, see Valian, 2015). In the framework of the ICM, for example, this is represented by control processes between language schemas.…”
Section: Processing Stages Outside Of Language Processingmentioning
confidence: 99%
“…Weissberger et al (2012) observed an increase of task mixing cost (color/shape decision) with increasing age when testing English-Spanish bilinguals, whereas task switch costs did not. With respect to language switching (digit naming in L1/L2), both mixing costs (see also , 2015 and switch costs (see also Gollan & Ferreira, 2009) increased with age. In summary, these aging studies seem to indicate little overlap between language and task switching.…”
Section: Processing Stages Outside Of Language Processingmentioning
confidence: 99%
“…This question is particularly pertinent to current controversies surrounding the exact type of tasks in which a “bilingualism effect” can be detected. Although, as discussed above, there is a considerable controversy as to whether cognitive differences between monolinguals and bilinguals exist at all, there is a broad consensus that if such differences exist, they would be found above all in the area of executive functions (Bak, 2016a, Valian, 2015). …”
Section: Introductionmentioning
confidence: 99%